Impact of football clubs on the recreational activities of preschoolers - GALAN, YAROSLAV; YARMAK, OLENA; ANDRIEIEVA, OLENA; MOSEYCHUK, YURIY; SUKHOMLYNOV, RUDOLF; ZORIY, YAROSLAV; KOSHURA, ANDRII; IVANCHUK, MARIYA; VASKAN, IVAN; BOHDANYUK, ANTONINA (Journal of Physical Education and Sport, 2021)
This article presents analysis of the impact of a recreational and health-promoting program with elements of football on the physical condition of 6-year-old children at preschool educational institutions. The pedagogical experiment involved thirty-six 6-year-old boys who attended additional classes with elements of football 3 times a week. The experiment was conducted at Chernivtsi Children’s and Youth School No. 1; the classes were held by qualified football coaches with more than 10 years of experience in teaching at sports schools for children and youth. Research methods. Theoretical analysis of specialized scientific and methodical literature, anthropometric methods, physiological methods, confirmatory pedagogical tests. The study was conducted in full compliance with all requirements of bioethics. Findings. The performed experiment showed that most older preschoolers suffered from disharmony in physical development. This study confirmed boys’ biological development disorders and deviations in posture and musculoskeletal system. The use of various activities significantly improved the condition of visual analyzer. Thus, the binocular vision of boys improved by 27.8 % (p < 0.05), and visual acuity increased by 16.6 % (p < 0.05). We assessed changes in the condition of boys’ foot arch after the program and observed an increase in the share of children with a normal foot arch, i.e., by 25.0 % (p < 0.05) for the right foot and by 19.5 % (p < 0.05) for the left foot. Regular football classes positively affected the adaptive capabilities of an organism to physical loads. Summary. The proposed program can be used in the practical work by children’s and youth sports school coaches, specialists working at preschool educational institutions, instructors, and teachers.
Keywords: physical development, biological development, visual analyzer, physical fitness